A review on aluminum alloys produced by wire arc additive manufacturing (WAAM): Applications, benefits, challenges and future trends - Murat Sarıkaya; Dilara Başcıl Önler; Salih Dağlı; Selim Hartomacıoğlu; Mustafa Günay; Grzegorz M. Królczyk (Journal of Materials Research and Technology)
Metal additive manufacturing is advancing with increasing momentum and attracting great attention. The Wire Arc Additive Manufacturing (WAAM) process, one of the metal additive manufacturing methods, involves melting a filler wire with an electric arc and depositing metal droplets layer by layer along the planned path. Aluminum alloys produced by the WAAM process have been in high demand in the industry, especially in the last decade. The WAAM process stands out as a suitable method for many industries due to its low investment cost, high deposition rates and the advantages of creating relatively complex parts. Key application areas of aluminum alloys produced using WAAM include aerospace, automotive, marine, and energy sectors, where lightweight structures, corrosion resistance, and high strength are critical. Much research has been done and innovative applications, including hybrid systems, have been developed to prevent defects such as residual stresses, cracks, porosity and delamination. This review article provides a comprehensive overview of the use of the WAAM process in aluminum alloys over the past decade. In the article, firstly, aluminum alloys, the WAAM technique and its types are introduced. In the following section, the methods used to improve mechanical properties and optimize the microstructure are examined in detail. In the next section, the difficulties encountered when using aluminum alloys in WAAM applications are discussed in detail. In the discussion section, current developments are evaluated, and in the last section, suggestions for future studies and inferences obtained from this study are presented. As a result, WAAM-CMT and hybrid systems were found to be effective in reducing defects such as porosity, distortion and residual stress. In addition, post-processing heat treatments and surface treatment methods are also crucial for improving mechanical properties. Finally, more research is needed in the areas of 7xxx series alloys, repair applications and environmental sustainability.